Terahertz photonics : 12-14 November 2007, Beijing, China - Zhang, Cunlin; Zhang, Xi-Cheng; The International Society for Optical Engineering; Society of Photo-Optical Instrumentation Engineers (Bellingham, Wash. : SPIE, 2008)
40